Anti-predator meshing may provide greater protection for sea turtle nests than predator removal. - Julie M O'Connor; Colin J Limpus; Kate M Hofmeister; Benjamin L Allen; Scott E Burnett (PLoS ONE)
The problem of how to protect sea turtle nests from terrestrial predators is of worldwide concern. On Queensland's southern Sunshine Coast, depredation of turtle nests by the introduced European red fox (Vulpes vulpes) has been recorded as the primary terrestrial cause of egg and hatchling mortality. We investigated the impact of foxes on the nests of the loggerhead turtle (Caretta caretta) and occasional green turtle (Chelonia mydas) over ten nesting seasons. Meshing of nests with fox exclusion devices (FEDs) was undertaken in all years accompanied by lethal fox control in the first five-year period, but not in the second five-year period. Lethal fox control was undertaken in the study area from 2005 to February 2010, but foxes still breached 27% (range19-52%) of turtle nests. In the second five-year period, despite the absence of lethal fox control, the average percentage of nests breached was less than 3% (range 0-4%). Comparison of clutch depredation rates in the two five-year periods demonstrated that continuous nest meshing may be more effective than lethal fox control in mitigating the impact of foxes on turtle nests. In the absence of unlimited resources available for the eradication of exotic predators, the use of FEDs and the support and resourcing of a dedicated volunteer base can be considered an effective turtle conservation tool on some beaches.